Speech activity as a purpose and means of teaching a foreign language - Voronova, Ye. M.; Воронова, Є. В.; Воронова, Е. М. (Харківський національний автомобильно-дорожній університет, 2019)
The article aims at highlighting the logical construction as a main feature of a foreign language lesson. Three compulsory aspects are shown to create the logic of a foreign language lesson. The importance of the active role of students while learning is shown.
Мовна діяльність як мета і засіб навчання іноземної мови
Речевая деятельность как цель и средство обучения иностранному языку
Keywords: discourse; speech activity; independent thinking; goal; invariant; collective communication; дискурс; мовна діяльність; самостійність мислення; чіткість мети; інваріант; колективне спілкування; мовотворчість; цілеспрямованість; дискурс; речевая деятельность; самостоятельность мышления; цель; инвариант; коллективное общение; речетворчество; 81'243=111